Comparison of automated three-dimensional volumetry with manual volumetry for graft evaluation before living donor liver transplant - A prospective study - Sanjay Sharma; Priya Ranjan; Sween Sheoran; Pankaj P. Rao; Dronacharya Routh (Journal of Current Research in Scientific Medicine, 2025)
Background: The aim of the study was to compare the accuracy and efficacy of automated three-dimensional (3D) software-aided computed tomography (CT) volumetry and manual CT volumetry in calculating the graft weight of living-donor livers for liver transplant (LT) with actual graft obtained during surgery. Materials and Methods: A total of 27 volunteer donors for LT were evaluated and operated at an LT Center from 2014 to 2017. Triple-phase contrast-enhanced computed tomography was done for all the donors and their graft liver volumes were calculated manually and by an automated postprocessing software. The residual liver volume was also calculated automatically with remnant percentage of total volume. Donor hepatectomies were performed as per the standard procedure. Graft volume requirement is assessed preoperatively based on body weight and Graft Recipient Weight Ratio >0.8 of the recipient. The correlation of graft weight calculated by these two methods was done against actual graft weights (AGWs) during surgery to evaluate the exact accuracy and efficacy of these preoperative measurements. Results: The average total liver volume (TLV) by the automated 3D method was 1207.22 cc (range 785–1596 cc), while the average TLV by the manual method was 1286 cc (range 904.7–1590 cc). The mean graft volume calculated by 3D-automated method and manual volumetry was 581.96 cc and 610.70 cc, respectively, while AGW calculated was 562.55 g. The mean difference between graft volume calculated by 3D-automated volumetry method and AGW was 19.40 g, while the mean difference between graft volume calculated by the manual volumetry method and AGW was 48.14 g. Conclusion: Manual volumetry and 3D-automated volumetry methods were both efficient and precise in measuring and predicting the graft volumes (TLV, standard liver volume, and future liver remnant) in living donor LT.